2021
DOI: 10.1097/rct.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Histogram Analysis of T2-Weighted and Diffusion-Weighted Magnetic Resonance Images for Prediction of Malignant Thymic Epithelial Tumors

Abstract: Purpose: To assess the value of histogram analysis for differentiating a high-risk thymic epithelial tumor (TET) from a low-risk TET using T2-weighted images and the apparent diffusion coefficient (ADC).Methods: Forty-nine patients with histopathologically proven TET after thymectomy were enrolled in this study and retrospectively classified as having low-risk TET (low-risk thymoma) or high-risk TET (high-risk thymoma or thymic carcinoma). Twelve parameters were obtained from the quantitative histogram analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…Of the 32 cases in this study in which ADC values were obtained, there was no significant difference in ADC values between stage I-II and stage III-IV tumors. In contrast to our results, several previous studies have found a significant difference in ADC values of TETs between Masaoka-Koga or Masaoka stage I-II and stage III-IV but differ as to whether the ADC values of stage III-IV tumors are significantly higher [ 23 ] or significantly lower [ 24 26 ] as compared to stage I-II tumors. Variability in results of these studies may relate to the differences in the placement of the ROI or volume of interest (VOI).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Of the 32 cases in this study in which ADC values were obtained, there was no significant difference in ADC values between stage I-II and stage III-IV tumors. In contrast to our results, several previous studies have found a significant difference in ADC values of TETs between Masaoka-Koga or Masaoka stage I-II and stage III-IV but differ as to whether the ADC values of stage III-IV tumors are significantly higher [ 23 ] or significantly lower [ 24 26 ] as compared to stage I-II tumors. Variability in results of these studies may relate to the differences in the placement of the ROI or volume of interest (VOI).…”
Section: Discussioncontrasting
confidence: 99%
“…Inoue et al similarly reported significant differences in heterogeneous signal intensity on T1- and T2-weighted images and intratumor low-signal foci on T2-weighted image which may reflect tumor degeneration seen in histologically high-grade TETs, especially thymic carcinoma [ 11 ]. Morikawa et al reported that although the T2 minimum value on histogram analysis did not show significant differences in differentiating histological classification, the T2 minimum values were significantly lower in Masaoka-Koga stage III-IV than stage I-II [ 23 ]. Similar to previous reports [ 2 , 11 ], there was a significant correlation between the TNM classification and the WHO histological classification in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation